Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
Step-by-step explanation:
6x - 9y = 12
subtract 6x from both sides
-9y = 12 - 6x
divide both sides by -9
y = -4/3 + 2/3x
or
y = 2/3x - 4/3
The equation 6x – 9y = 12 written in terms of y is; y = (2/3)x - 4/3
- We are required to write the equation 6x – 9y = 12 in terms of y.
Rewriting the equation 6x – 9y = 12 in terms of y is as follows;
- 6x – 9y = 12
- 6x - 12 = 9y
Divide through by 9 so that we have;
y = (2/3)x - 4/3
Read More on Change of formula subject:
https://brainly.com/question/9584546
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.